The Image of the Soviet Man in Svetlana Alexievich’s Novel „Chernobyl Prayer: a Chronicle of the Future” - Stępniak, Anna (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2019)
The paper is concerned with the documentary novel by Svetlana Alexievich which describes one of the biggest technological humanitarian disasters of the 20th century: the catastrophic accident at the Chernobyl Nuclear Power Plant. The attention is focused on the portraiture of the soviet man – of the heroes of the event, who survived the catastrophe but have been left without any help from the institutions and people they had relied on: the government and the country. The book provides the testimony of the witnesses: in this polyphonic form Alexievich lets them speak for themselves. The victims of the disaster have paid the highest price: they have lost everything – their lives, their relatives and hopes for the future.